Identifikasi Hambatan Penyelesaian Studi Bagi Mahasiswa Program Studi PJKR STKIP Simbiosis - Segi, Longginus (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
PJKR STKIP Symbiosis students complete their studies for an average of 4 years to 6 years. This research was conducted for the purpose of finding out the obstacles for PJKR STKIP Symbiosis students in completing their studies on time (4 years or less than 4 years). This type of research is mixed (quantitative descriptive and qualitative). The population in this study were PJKR STKIP Symbiosis students. The instruments used in this research were closed and open questionnaires. The data analysis technique uses descriptive statistics and qualitative analysis. The results of quantitative descriptive research were obtained as follows, namely: very low barriers for 55 students (60.44%), low barriers for 32 students (35.16%), and moderate barriers for 4 students (4.40%). Based on the results of the qualitative research, there are 4 conclusions regarding obstacles to completing lectures on time, namely 1) students themselves are less active in lectures so that many courses are not passed, 2) During the Covid-19 pandemic, many students experience problems in finding book references to write a research proposal, 3) some theoretical lecture material related to the preparation of final assignments such as statistics and research methodology which is delivered online is not mastered and understood by students, and 4) "The lack of complete facilities on the Wates campus causes the lecture process to be less effective so that knowledge obtained less than optimal. For example, there is no basketball court and incomplete sports equipment, so many parts are overlooked.